DESIGNING SCIENCE UNITS OF STUDY - Ediger, Marlow (SCHOOL SCIENCE, 2013)
To design the curriculum area of science, careful attention needs to be given to the structure of unit planning. The objectives for students to attain may be stated in measurable terms. To achieve balance in the curriculum, cognite, affective and psychomotor ends need to be stated with precision. Each domain of objectives is salient for student attainment. After instruction, it is possible to measure if a learner has or has not achieved the measurably stated objective. Toward the other end of the continuum, general objectives may be stated and implemented in ongoing units of study. To stress balance among general objectives, understandings, skills and attitudinal goals should be emphasised in teaching-learning situations. With general objectives, it is not possible to measure if a student has or has not achieved the chosen end. However, flexibility in curriculum development may be emphasised, such as student-teacher planning.